Uses of Gramsci in the Contemporary Greek Context - Sotiris, Panagiotis (International Gramsci Journal, 2023)
This is the abstract of the article in English by Panagiotis Sotiris on the state of Gramsci work in Greece and on the Greek left’s relation to Gramscian notions. We give his own English-language presentation of the article here below as an extended Abstract. Presentation This presentation offers an overview and discussion of how the work of Antonio Gramsci, and notions and themes stemming from it, have been used in the context of political, strategic, and theoretical debates in Greece since the second half of the 2000s. What emerges is a situation where despite the widespread use of notions and themes coming from Gramsci, there is not extensive reference or dialogue with the more recent Gramsci research and scholarship, and nor has a more ‘native’ tradition of Gramsci Studies emerged. However, both political-strategic and theoretical debates could benefit from engagement with Gramsci in that direction, especially since the particular Greek conjuncture after 2010 points to the continuing pertinence of Gramscian notions as means to analyse social and political dynamics and exigencies, but also to deal with open theoretical questions in the field of the Social Sciences.